Pengaruh Mulligan Exercise Terhadap Peningkatan Lingkup Gerak Sendi Lutut Pada Lanjut Usia - Ichsandri, Haiban; , Isnaini Herawati, S.Fis., M.Sc (2016)
Background: Seniors (Elderly) is a period in which the organism has reached maturity in size and functionality and also have shown deterioration over time, the elderly will be a process of disappearance of the network's ability to selfrepair or replace and maintain normal function slowly so unable to fight infection and repair the damage. The decrease of motion in the elderly may be due to problems in the joints, contractures. In the elderly knee joint as much as 25% experienced stiffness in flexion. The stiffness can be caused by calcification in elderly will reduce the flexibility of the joints. Some treatments can be given to help reduce the limitations of a movement disorder caused by the degenerative process, one of which is to provide exercise Mulligan. Objective: This study aimed to determine whether there is influence of Mulligan exercise to increase the limited range of motion of the knee joint in the elderly. Methods: This research is a pre-experimental study using Quasiexperimental approach to the design of the study pre and post test design group to determine the effect of exercise to increase Mulligan limited range of motion of the knee joint in the elderly. The sample in this study of 40 people were taken through purposive sampling method, measurements of motion in this study using a goniometer. Results: correlative test Wilcoxon test on the test results pemberianMulligan exercise influence on the increase in the scope of the limitation of the knee joint in the elderly get significant value of p <0.05, which means there pemberianMulligan exercise influence on the increase in the limited scope of the knee joint in the elderly (p = 0.000). Conclusion: There is Mulligan exercise have a influence on the increase in the limited scope of the knee joint in the elderly. Keywords: Elderly, Mulligan exercise, limitation of motion